ROBUST FLICKERS OF FREEDOM. Issue 1 (2019) - Robinson, Michael
Abstract: This essay advances a version of the flicker of freedom defense of the Principle of Alternative Possibilities (PAP) and shows that it is invulnerable to the major objections facing other versions of this defense. Proponents of the flicker defense argue that Frankfurt-style cases fail to undermine PAP because agents in these cases continue to possess alternative possibilities. Critics of the flicker strategy contend that the alternatives that remain open to agents in these cases are unable to rebuff Frankfurt-style attack on the grounds that they are insufficiently robust (that is, morally significant in a way that could ground ascriptions of moral responsibility). Once we see that omissions are capable of constituting robust alternatives, even when they are not intentional, it becomes clear that agents in these cases do indeed possess robust alternative possibilities—alternatives that are ineliminable from cases of this sort. The upshot is that Frankfurt-style cases are theoretically incapable of providing us with good grounds for rejecting PAP.